ACM SIGDOC European Chapter/ Eurosigdoc Workshop on Open Source and Design of Communication - OSDOC '10 - Costa, Carlos, J.; Protopsaltis, Aristidis (2010)

Adaptive User-Centric Experiences in Virtual Environments: Levels of Interactions - Panzoli, David; Peters, C; Dunwell, Ian; Sanchez, S, S; Petridis, Panagiotis; Protopsaltis, Aristidis; Scesa, V; De Freitas, Sara (The 13th International Conference on Computer Graphics and Artificial Intelligence (3IA, 2010)

A level of interaction framework for exploratory learning with characters in virtual environments - Panzoli, David; Peters, Christopher; Dunwell, Ian; Sanchez, Stéphane; Petridis, Panagiotis; Protopsaltis, Aristidis; Scesa, Vincent; De Freitas, Sara (Intelligent Computer Graphics 2010, 2010)
This paper investigates a range of challenges faced in the design of a serious game aimed at teaching history in situ, through the use of an immersive, open virtual environment. In the context of this paper, such an environment is described as an exploratory, expansive virtual world within which a user may interact in a non-linear and situated fashion with the virtual characters that populate it. The main contribution of this paper consists of the introduction of the Levels of Interaction (LoI) framework, designed to assist in the creation of multiple forms of interaction between a user-driven avatar and synthetic characters. The LoI approach addresses the necessity for balancing computational efficiency with the need to provide believable and interactive virtual characters, allowing varying degrees of visual, interactive and behavioural fidelity. The Roma Nova project demonstrates a first implementation of the concept, showing in practice how the LoI are likely to foster more natural interactions between the player and the non-playing characters. © 2010 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up

A Social Innovation Serious Game for Higher Education - Schorer, Antonia; Pouliopoulos, Theofilos; Garefi, Ioanna; Kalemaki, Irene; Galvan, Cristina; Barajas, Mario; Theodoridou, Katerina; Kouros, Thodoris; Fuduric, Morana; Papa, Venia; Mavrogeni, Stavroula; Wittine, Zoran; et al. (International Social Innovation Research Conference, 2022)
Engaging in social innovation education and practices often leads to a challenging experience of the social value behind the efforts for the addressed target groups. In particular, it is a question of what the individual's efforts could achieve not only at the micro level but also for the present and future common good. In this context, it is relevant for higher education to strengthen students' self-efficacy and to convince them that their skills and resources are capable of influencing social change in innovative ways. In order to support students in this area and to sensitise them to the concerns of the future of society, a serious game is being developed dealing with these aspects in an appropriate didactic and game-based approach. As part of the H2020 project Nemesis, a serious game for the school sector has already been developed that addresses the topic of social innovation. For the BUFSIE project a new Serious Game is being developed to address the needs of social innovation education in higher education. The game is based on the NEMESIS Serious Game but it is now further developed and adapted to the needs of higher education within the Erasmus+ Project BUFSIE. Through a co-design session with university lecturers, the scenarios were analysed and designed in line to the target group needs. The game consists of 7 missions related to different sustainable development goals, covering different areas of interest in relation to social innovation. The main purpose of the game is to actively engage with the topic of social innovation, to raise awareness of the concerns of the social future in the sense of empathy, to promote self-efficacy expectations and to foster a positive emotional learning experience. In order to achieve these goals, the game logic combines open world games and adventure games in order to guarantee the maximum freedom, and use the potential for knowledge transfer of adventure games (puzzles, dialogues with non-player characters NPCs, and a game story). The game will be available in 5 European languages (DE, GR, HR, CY, ES) as web-based application and for smart devices. The technical implementation is carried out with the development environment Unity 3D. This enables to realize the game in a high quality and offer it to the target group in different formats (e.g. as a browser game or app) according to their needs. To create the game with the characteristic features of adventure games, the plug-in AdventureCreatore (Icebox Studios) is utilised. As part of the technical development, the scenes for the different game missions are graphically realised and the game mechanisms and functions implemented. In addition, menu elements are developed to offer the possibility to save and load the game state, to change the language, to switch music on and off and to receive further information about the game and the BUFSIE project. The finished version of the game will be intensively tested by students, institute members and consortium partners for malfunctions on various devices with different requirements to ensure that the game can be used in the higher education institution in a stabile way and without interference. Finally, the game will be evaluated at 5 higher education institutions across Europe to determine the usability and playability of the game as well as the intended learning outcome

Assessing the impact of Social Innovation Education on student’s engagement - Garefi, Ioana; Kalemaki, Irene; Protopsaltis, Aristidis (Proceedings 8th International Conference On Sustainable Development, 2020)
This paper presents the findings of the H2020 NEMESIS project that aims to design, test and validate a consolidated approach for embedding Social Innovation in Education. Social Innovation Education (SIE) is a new educational approach that aims to empower students to take action for a more democratic and sustainable society. During the academic year 2018-2019, eight schools from five European countries applied the NEMESIS SIE framework by involving 56 teachers, 1030 students and 69 community members in a variety of SIE approaches. This paper reports on these attempts with a particular focus on analyzing their impact on student's engagement. Data were retrieved through focus groups with 80 people, an online survey to 206 students, interviews, classroom observations and students' narratives. Research findings suggested positive outcomes for students in terms of emotional, cognitive, behavioral and agentic engagement. Findings also showed a positive influence of SIE on the cultivation and progression of students' social innovation competences. These initial findings have the potential to pave the way for more research in the under-investigated field of SIE as well as to encourage policies and initiatives for promoting social innovation in education.</
Keywords: Social Innovation; Education; impact; cognitive; behavioural; emotional; agentic engagement

Assessing the impact of Social Innovation Education on student’s engagement. European Journal Of Sustainable Development - Kalemaki, Irene; Garefi, Ioana; Protopsaltis, Aristidis (European Journal of Sustainable Development, 2021)
This paper presents the findings of the H2020 NEMESIS project that aims to design, test and validate a consolidated approach for embedding Social Innovation in Education. Social Innovation Education (SIE) is a new educational approach that aims to empower students to take action for a more democratic and sustainable society. During the academic year 2018-2019, eight schools from five European countries applied the NEMESIS SIE framework by involving 56 teachers, 1030 students and 69 community members in a variety of SIE approaches. This paper reports on these attempts with a particular focus on analyzing their impact on student's engagement. Data were retrieved through focus groups with 80 people, an online survey to 206 students, interviews, classroom observations and students' narratives. Research findings suggested positive outcomes for students in terms of emotional, cognitive, behavioral and agentic engagement. Findings also showed a positive influence of SIE on the cultivation and progression of student s' social innovation competences. These initial findings have the potential to pave the way for more research in the under investigated field of SIE as well as to encourage policies and initiatives for promoting social innovation in education This paper presents the findings of the H2020 NEMESIS project that aims to design, test and validate a consolidated approach for embedding Social Innovation in Education. Social Innovation Education (SIE) is a new educational approach that aims to empower students to take action for a more democratic and sustainable society. During the academic year 2018 - 2019, eight schools from five European countries applied the NEMESIS SIE framework by involving 56 teachers, 1030 students and 69 community members in a va riety of YOU approaches. This paper reports on these attempts with a particular focus on analyzing their impact on student's engagement. Data were retrieved through focus groups with 80 people, an online survey to 206 students, interviews, classroom observ ations and students' narratives. Research findings suggested positive outcomes for students in terms of emotional, cognitive, behavioral and agentic engagement. Findings also showed a positive influence of SIE on the cultivation and progression of student s' social innovation competences. These initial findings have the potential to pave the way for more research in the under investigated field of SIE as well as to encourage policies and initiatives for promoting social innovation in education
Keywords: Social Innovation; Education; impact; cognitive; behavioural; emotional; agentic engagement

Attain Cultural Integration through teachers' Conflict Resolution skills Development: The ACCORD Project - Marocco, Davide; Dell'Aquila, Elena; Zurlo, Maria Clelia; Vallone, Federica; Barajas, Mario; Frossard, Frederique; Di Ferdinando, Andrea; Di Fuccio, Raffaele; Lippens, Michiel; Van Praag, Lore; Protopsaltis, Aristidis; Swertz, Christian; et al. (QWERTY, 2019)
Scenario-based learning (SBL) has recently received more and more attention in the training and education fields as a mechanism for providing active and generative learning. E-learning systems can provide a solid platform upon which SBL can be created and used to promote relational competences development, and to offer open source e-learning tools so to overcome common lack of access to affordable training resources. Within this paper a project called ACCORD to develop a new e-learning system to promote intercultural skills in terms of intercultural literacy, inclusive education and conflict management will be described. This project aims to prepare secondary school teachers from five European countries (Austria, Belgium, Germany, Italy, Spain) to take an active stand against intercultural conflicts within the school context, by providing SBL and game-based learning approach. The present article will provide an overview of the ACCORD project, highlighting the theoretical framework underpinning its development, the methodologies that have been used, and the main preliminary outcomes.
CRIS-Team WoS Importer:2020-02-18

Authoring of Adaptive Serious Games - Hendrix, Maurice; Knutov, Evgeny; Auneau, Laurent; Protopsaltis, Aristidis; Arnab, Sylvester; Dunwell, Ian; Petridis, Panagiotis; de Freitas, Sara (7th European Conference of Technology Enhanced Learning, EC-TEL 2012, 2012)
Game-based approaches to learning are increasingly being recognized as having the potential to stimulate intrinsic motivation amongst learners. Whilst a range of examples of effective serious games exist, creating the high-fidelity content with which to populate a serious game is resource-intensive task. To reduce this resource requirement, research is increasingly exploring means to reuse and repurpose existing games and relevant sources of content. Education has proven a popular application area for Adaptive Hypermedia, as adaptation can offer enriched learning experiences to students. Whilst content to-date has mainly been in the form of rich text, various efforts have been made to integrate Serious Games into Adaptive Hypermedia via run-time adaptation engines. However, there is little in the way of effective integrated authoring and user modeling support for these efforts. This paper explores avenues for effectively integrating serious games into adaptive hypermedia. In particular, we consider authoring and user modeling aspects in addition to integration into run-time adaptation engines, thereby enabling authors to create Adaptive Hypermedia that includes an adaptive game, thus going beyond mere selection of a suitable game and towards an approach with the capability to adapt and respond to the needs of learners and educators.<br
Keywords: Adaptive Hypermedia; Adaptation; Serious Games; Educational Games; Education Personalization

Automating Content Generation for Large-Scale Virtual Learning Environments using Semantic Web Services - Dunwell, Ian; Petridis, Panagiotis; Protopsaltis, Aristidis; de Freitas, Sara; Panzoli, David; Samuels, Peter (proceedings of the 5th International Workshop on Semantic Wikis (SemWiki2010), 2010)

Behavioural and attitudinal change in Serious Games used for Environmental purposes - Pisipunth, C.; Petridis, Panagiotis; Lamera, Petros; Hendrix, Moris; Protopsaltis, Aristidis; Dunwel, Ian; Arnab, Sylvester; de Freitas, Sara (Simulation and Gaming, 2013)

Blended game-based learning environments: Extending a serious game into a learning content management system - Dunwell, Ian; Petridis, Panagiotis; Arnab, Sylvester; Protopsaltis, Aristidis; Hendrix, Maurice; De Freitas, Sara (Proceedings - 3rd IEEE International Conference on Intelligent Networking and Collaborative Systems, INCoS 2011, 2011)
Serious games have recognized potential as a means to tackle many challenges in education, ranging from stimulating increased learner motivation, to transferring challenging concepts in a novel and engaging form. They are commonly shown to work most effectively in blended approaches to learning, whereby the game plays a core role in a wider pedagogic approach, often based around an experiential or exploratory model. In this paper, we explore how the integration of a serious game, and more generally gaming paradigms, can be extended to a learning content management system (LCMS) to support a blended and holistic approach to their use in education. Through a case study within the EU-Funded Adaptive Learning via Intuitive/Interactive, Collaborative and Emotional Systems (ALICE) project, we demonstrate a technical integration of a gaming engine with a proprietary LCMS, and discuss the broader pedagogic benefits of such an approach. In particular, we note how this method can support an 'intuitive guided' or scaffolded approach to learning, where the learner is given the potential to explore a non-linear learning environment, whilst scaffolding and blending provides the guidance towards ensuring targeted learning objectives are met. © 2011 IEEE.
Created from Fastlane, Scopus look-up
Keywords: Blended learning; Game-based learning; Learning content management systems; Pedagogy; Serious games; Technology enhanced learning

Building social commmunities around alternate reality games - Petridis, Panagiotis; Dunwell, Ian; Arnab, Sylvester; Scarle, Simon; Qureshi, Adam; De Freitas, Sara; Protopsaltis, Aristidis; Star, Kam (Proceedings - 2011 3rd International Conferenceon Games and Virtual Worlds for Serious Applications, VS-Games 2011, 2011)
In recent years, alternate reality games have entered the mainstream as a new form of entertainment. The Living Stories project is the first alternate reality game in the UK, which addresses environmental issues. Living Stories combines social networking sites such as Facebook and Twitter with Second Life, to create a platform, which allows social networking to feed into content creation within a virtual world, and facilitate and encourage real-world behaviour through virtual rewards. The project is funded by Interactive Digital Media IDM, as part of an ongoing collaboration with the Eden Project, Coventry University Serious Games Institute and PlayGen Ltd. The aim of this project is twofold: firstly to engage new visitors and to extend the Eden experience beyond the actual visits, and secondly to increase user participation amongst groups that do not traditionally visit Eden Project. In this paper we describe the unique technical and pedagogic challenges addressed when creating this platform and consider how the state-of-the-art in alternate reality gaming can be applied in an educational ('serious') context. © 2011 IEEE.
Created from Fastlane, Scopus look-up
Keywords: Alternate reality; Mixed reality; Serious games

Cognitive Aspects of Web-based Hypertext: An experimental approach - Protopsaltis, Aristidis; Bouki, Vassiliki (3rd WSEAS Int. Conference on E-Activities, 2004)

Cognitive Aspects of Web-based Hypertext: An experimental approach - Protopsaltis, Aristidis; Bouki, Vasiliki (WSEAS Transactions on Information Science and Applications, 2004)

Cognitive Model for Web Based Hypertext Comprehension - Protopsaltis, Aristidis; Bouki, Vasiliki (6th IASTED Int. Conference on Web-Based Education 2004, 2004)

Comprehension of an electronic document- what readers do and do not do - Protopsaltis, Aristidis; Bouki, Vasiliki (The Sixteenth Triennial Conference of the International Federation of Operational Research Societies, 2002)
This study aims to investigate the cognitive aspects of discourse processing in an electronic environment with the use of think-aloud protocols. This study is a pilot study and it is part of a more extensive research. A cognitive model has been proposed to account for reading comprehension in an electronic environment. An experiment has been designed to assess this model. The objectives of the experiment are to study the cognitive processes and the reading strategies that are necessary during the reading of information on the WWW. Eight subjects have taken part in this pilot phase of the experiment. The subjects read the document for as long as they felt confident that could answer questions about it. All subjects answer the same set of question

Creative Learning with Serious Games - Guest Editorial - Protopsaltis, Aristidis; Pannese, Lucia; Hetzner, Sonia; Dimitra, Pappa; de Freitas, Sara (International Journal of Emerging Technologies in Learning, 2010)
This paper, summarises the Creative Learning with Serious Games workshop that took place in the Fun and Games 2010 conference. The workshop discussed innovative methodological approaches to Serious Games for creative learning. A special emphasis was given to state-ofthe- art research work and cross-discipline approaches (e.g. the mix of Storytelling and Serious Games). In addition, different case studies coming from very different European(research) projects were presented and discussed with the participants. Five papers were selected via a peer reviewed process to be presented at the workshop. The authors presented their work and demonstrated their applications during the second part of the workshop. <br
Keywords: Storytelling; Experiential Learning; Creative learning; Serious games; Game-Based Learning

Creative thinking experimentations for entrepreneurship with a disruptive, personalised and mobile game-based learning ecosystem - Lameras, Petros; Tsiatsos, Thrasyvoulos; Petridis, Panagiotis; Tolis, Dimitris; Liarokapis, Fotis; Anastasiadou, Despina; Protopsaltis, Aristidis; Hendrix, Maurice; Arnab, Sylvester (Proceedings of 2015 International Conference on Interactive Mobile Communication Technologies and Learning, IMCL 2015, 2015)
Based on an unprecedented need of stimulating creative capacities towards entrepreneurship to university students and young researchers, this paper introduces and analyses a smart learning ecosystem for encouraging teaching and learning on creative thinking as a distinct feature to be taught and learnt in universities. The paper introduces a mashed-up authoring architecture for designing lesson-plans and games with visual learning mechanics for creativity learning. The design process is facilitated by creativity pathways discerned across components. Participatory learning, networking and capacity building is a key aspect of the architecture, extending the learning experience and context from the classroom to outdoor (co-authoring of creative pathways by students, teachers and real-world entrepreneurs) and personal spaces. We anticipate that the smart learning ecosystem will be empirically evaluated and validated in future iterations for exploring the benefits of using games for enhancing creative mindsets, unlocking the imagination that lies within, practiced and transferred to multiple academic tribes and territories.
Created from Fastlane, Scopus look-up
Keywords: Creative mindsets; Creativity; Disruptive mobile games; Entrepreneurship; Higher education; Problem-based learning

Defining a metadata schema for serious games - Protopsaltis, Aristidis; Hendrix, Maurice; Dunwell, Ian; de Freitas, Sara; Arnab, Sylvester; Petridis, Panagiotis; Rolland, S; Llanas, J (Fourth International Conference on Mobile, and On-line Learning Hybrid, 2012)

Digi-Teachers: Technology and Practice - Goodwyn, Andrew; Fuller, Carol; Protopsaltis, Aristidis (Annual Meeting of the American Educational Research Association (AERA 2010), 2010)

Does Gender Matter in Hypertext Reading? - Protopsaltis, Aristidis; Bouki, Vasiliki (Proceedings of EdMedia + Innovate Learning 2008, 2008)

E-commerce transactions in a virtual environment: Virtual transactions - Scarle, Simon; Arnab, Sylvester; Dunwell, Ian; Petridis, Panagiotis; Protopsaltis, Aristidis; De Freitas, Sara (Electronic Commerce Research, 2012)
E-commerce is a fundamental method of doing business, such that for a firm to say it is trading at all in the modern market-place it must have some element of on-line presence. Coupled with this is the explosion of the "population" of Massively Multiplayer On-line Role Playing Games and other shared virtual environments. Many suggest this will lead to a further dimension of commerce: virtual commerce. We discuss here the issues, current roadblocks and present state of an e-commerce transaction carried out completely within a virtual environment; a virtual transaction. Although technically such transactions are in a sense trivial, they raise many other issues in complex ways thus making V-transactions a highly interesting cross-disciplinary issue. We also discuss the social, ethical and regulatory implications for the virtual communities in these environments of such v-transactions, how their implementation affects the nature and management of a virtual environment, and how they represent a fundamental merging of the real and virtual worlds for the purpose of commerce. We highlight the minimal set of features a v-transaction capable virtual environment requires and suggest a model of how in the medium term they could be carried out via a methodology we call click-through, and that the developers of such environments will need to take on the multi-modal behavior of their users, as well as elements of the economic and political sciences in order to fully realize the commercial potential of the v-transaction. © 2012 Springer Science+Business Media, LLC.
Created from Fastlane, Scopus look-up
Keywords: E-commerce; Electronic commerce; Metaverses; Virtual environments; Virtual worlds

EdCCDroid: An Education Pilot Prototype for Introducing Code-Combat using LUA - Wood, C.; Mentzelopoulos, M.; Protopsaltis, Aristidis (2015)

EdCCDroid: An Education Pilot Prototype for Introducing Code-Combat using LUA - Wood, Conor; Mentzelopoulos, Markos; Protopsaltis, Aristidis (Workshop Proceedings of the 11th International Conference on Intelligent Environments, 2015)

Effects of Serious Games and game-based learning on learners' achievement emotions - Schorer, Antonia; Protopsaltis, Aristidis (Proceedings of the 14th European Conference on Game Based Learning ECGBL 2020, 2020)
The development of new skills and knowledge often leads to challenges. The emotional experience of the learner while confronted with the learning object is crucial for the learning process. Learners who approach a subject with interest and curiosity, and thus value the learning activity with positive emotions, achieve a more promising effect than people who perceive the content as boring, challenging and frightening. Providing positive learning experiences, is the main focus of serious games. Emotional experience, in relation to achievement activities in serious games, are not comprehensively addressed in the scientific debate (Pekrun, 2006; Loderer et al, 2019). In some, approaches which are conceptually closely linked to the perspectives of achievement emotion, for instance in terms of self-efficacy (Ketelhut, 2007; Meluso et al, 2012), are taken into account. The perceived self-efficacy of an individual can be seen in the sense of achievement emotion, as a cognitive evaluation process for a specific learning and achievement event and confirms the assumption that the use of serious games can affect learners' achievement emotions. The objective of this work is the theoretical analysis of the effects of game-based learning on the learner's achievement emotions and on whether the systematic use of serious games has a positive effect on existing negative mindsets. This research is part of an Horizon 2020 project called NEMESIS. The aim of the project is to combine education, technology and social innovation to sensitize today's youth to the social concerns and create the changemakers of the future. Through the use of the NEMESIS serious game, the expectation of self-efficacy is to be promoted, and awareness of the concerns of the social future and empathy is to be raised. This paper focuses on the theoretical consideration of the connection between serious games and achievement emotions in relation to the didactic conception of the game, in which the active engagement with the topic of social innovation and the emotional experience during the learning process is addressed.<br
Keywords: Games; Game-based Learning; achievement emotions; social innovation; self-efficacy:

Explosive ordinance disposal: Motion sensor simulator in Nintendo Wii - Mentzelopoulos, Markos; Tanasa, Mihai; Protopsaltis, Aristidis; Economou, Daphne (SIGDOC'11 - Proceedings of the 29th ACM International Conference on Design of Communication, 2011)
Simulation based games attempt to replicate real life or fiction scenarios for the purposes of learning, training, investigating or predicting results. This paper presents a case study of a simulation based on terrestrial which are primarily used by Explosive Ordinance Disposal Units (E.O.D.) in the investigation and disposal of bomb threats in Nintendo Wii, to examine different methods and techniques of player immersion, adaptation and learning. The paper presents background research that has been conducted for the design and implementation of the E.O.D. simulator. The simulated environment demonstrates its usefulness over a number of real bomb scenarios where player has to actively inspect the environment to locate and dispose of any potential bomb threats in an efficient manner. © 2011 ACM.
Created from Fastlane, Scopus look-up
Keywords: aabb (axis aligned bounding box); avt (automatic video tracking); game engine; igs (image generators); object oriented; oobb (object aligned bounding box); peo stri (program executive office for simulation; training and instrumentation); sdk (software development kit); sivet (simulated infrared/visible engagements with targets); vr (virtual reality); xna pipeline

Game-based learning for knowledge sharing and transfer: the e-VITA approach for intergenerational learning - Hetzner, Sonia; Protopsaltis, Aristidis; Dimitra, Pappa; Dunwell, Ian; Pannese, Lucia; de Freitas, Sara; Rebolledo-Mendez, Genaro (Handbook of research on improving learning and motivation through educational games : multidisciplinary approaches, 2011)
Keywords: Serious Game; intergenerational learning; Game-based learning

Game-based Social Innovation Education in Primary and Secondary Education - Schorer, Antonia; Protopsaltis, Aristidis (Proceedings of 12th International Social Innovation Research Conference, 2022)
Developing new skills and knowledge through the use of serious games and game-based learning in the school environment as part of social innovation education offers the potential for forward-looking and promising opportunities. Social innovation education in schools can motivate and empower children and adolescents to engage as social change makers with relevance in primary as well as secondary education. Active participation in activities with social impact and the associated self-efficacy can be strengthened in particular through game-based learning formats and associated positive emotional learning experiences. Serious Games provide an authentic but protected environment to work on new and real problems through social innovation projects. Achieving the educational goals of the game at both primary and secondary level depends on the user experience of the children and adolescents during the playing and learning process. Usability and playability are key determinants of a positive game-based learning experience and it is important to consider if the same needs and conditions lead to similar results in different age groups or if age-specific aspects need to be taken into account in future conceptual designs. In order to be able to draw conclusions in this context, this paper presents and compares the results of the empirical analysis of the user experience of primary and secondary school learners in the Serious Game for Social Innovation Education and the related effects on learning outcomes. “The game, based on an adventure and open-world game, introduces social innovation to students. This is achieved by bringing the player to NEMESIS City with the aim of increasing the well-being of the inhabitants with his "social innovation power". There, the player gets the opportunity to work on new problems and implement social innovation projects in collaboration with non-player characters (teachers, social innovators, parents other stakeholders) in order to be rewarded with happiness points for the city” (Schorer & Protopsaltis 2021, p. 620). The game focuses on topics of social innovation education - such as social value creation, examples of social innovation, self-efficacy expectations or the importance of the UN Sustainable Development Goals. The evaluation process was conducted in three European schools (one primary school in UK, and two secondary schools in Greece and Romania) and the research design followed a pre- and posttest approach to evaluate the impact of the serious game in the areas of usability/ playability, narratives, play engrossment, enjoyment, creative freedom, personal gratification, visual aesthetics and learning succes
Keywords: Social Innovation Education; Game-based Learning; Serious Games; Education

Game Engines Selection Framework for High-Fidelity Serious Applications - Petridis, Panagiotis; Dunwell, Ian; Panzoli, David; Arnab, Sylvester; Protopsaltis, Aristidis; Hendrix, Maurice; de Freitas, Sara (International Journal of Interactive worlds, 2012)
Serious games represent the state-of-the-art in the convergence of electronic gaming technologies with instructional design principles and pedagogies. Despite the value of high-fidelity content in engaging learners and providing realistic training environments, building games which deliver high levels of visual and functional realism is a complex, time consuming and expensive process. Therefore, commercial game engines, which provide a development environment and resources to more rapidly create high-fidelity virtual worlds, are increasingly used for serious as well as for entertainment applications. Towards this intention, the authors propose a new framework for the selection of game engines for serious applications and sets out five elements for analysis of engines in order to create a benchmarking approach to the validation of game engine selection. Selection criteria for game engines and the choice of platform for Serious Games are substantially different from entertainment games, as Serious Games have very different objectives, emphases and technical requirements. In particular, the convergence of training simulators with serious games, made possible by increasing hardware rendering capacity is enabling the creation of high-fidelity serious games, which challenge existing instructional approaches. This paper overviews several game engines that are suitable for high-fidelity serious games, using the proposed framework. <br
Keywords: High Fidelity; Serious Games; Game Engines; Visualization

Gender and information processing in electronic age - Protopsaltis, Aristidis; Bouki, Vassiliki (SIGDOC 2008 - Proceedings of the 26th ACM International Conference on Design of Communication, 2008)
The effect of gender in academic achievement has often been the focus of research because of its potential implications. However, the Web has modified the way people access and use information. The present study examines the differences between males' and females' reading behaviour in hypertexts. The study focuses on text based electronic documents. Ninety participants (27 females and 63 males) read a hierarchically structured hypertext and answered a set of questions. The study examines some original variables not previously studied comprehensively, such as coherence of transactions, sum of selected hyperlinks, hyperlink location etc. The results show that gender did not significantly affect any of the measured variables. The data consisted of reading times, comprehension scores, coherent links, hyperlink location, sum of hyperlinks, and the sum of read nodes. Copyright 2008 ACM.
Created from Fastlane, Scopus look-up
Keywords: Cognitive processes; Coherence; Comprehension; Gender; Hyperlinks; Hypertext; Information processing; Reading

Gender Patterns in Hypertext Reading - Protopsaltis, Aristidis; Bouki, Vassiliki (Ergonomics Open Journal, 2009)
The effect of gender in learning has often been the focus of research because of its potential implications in academic achievement. However, the effect of gender in hypertext reading has not been thoroughly investigated. The Web in general and the hypertext in particular has modified the way people access and use information. This paper reports the findings of an empirical study into gender differences in hypertext reading. The study focuses on text-based electronic documents. The study is a mixed method design, with the use of the think-aloud protocols and a between subjects experiment. It examines some original variables not previously studied comprehensively, such as coherence of transactions, sum of selected hyperlinks, and hyperlink location. Forty two participants (30 males and 12 females) read a hierarchically structured hypertext and then, all answered the same set of questions. The data consisted of reading times, comprehension scores, reading strategies, coherent links, hyperlink location, sum of hyperlinks, and the sum of read nodes. The results show that gender did not significantly affect any of the measured variables.<br

Hardware Interfaces for VR Applications: Evaluation on Prototypes - Mentzelopoulos, M.; Tarpini, F.; Emanuele, A.; Protopsaltis, Aristidis (IEEE International Conference on Computer and Information Technology; Ubiquitous Computing and Communications; Dependable, Autonomic and Secure Computing; Pervasive Intelligence and Computing (CIT/IUCC/DASC/PICOM), 2015)

Harnessing Technology Strategy: Celebrating Outstanding teachers - Goodwyn, Andrew; Protopsaltis, Aristidis; Fuller, Carol L. (2009)

How Outstanding Teachers Make Creative Uses of Technology in their Teaching - Protopsaltis, Aristidis; Goodwyn, Andrew; Fuller, Carol (European Conference on Educational Research, Vienna (ECER 2009), 2009)

How to teach entrepreneurship using serious games and web 2.0 - Protopsaltis, Aristidis; Hetzner, Sonia; Borotis, Spiros; Connolly, Thomas; Hainey, Thomas (14th IEEE International Conference on Advanced Learning Technologies, ICALT 2014, 2014)
This paper reports on the main piloting of the StartUp_EU project (http://startup-eu.net/). StartUp_EU targets secondary schools and simulates the process of starting up a high tech company. The project developed a series of mini-games, a Web2.0 platform and a collaborative competition for students, between 14 and 18 years of age. 243 students participated in the competition, completing a series of 8 tasks, starting from a business idea to a product and creating an elevator pitch. Pre-competition and post-competition questionnaires were collected and the results on participants' perception of the learning experience regarding entrepreneurship using serious games and Web 2.0 technologies, presented here.
Keywords: game-based learning; entrepreneurship; serious games; secondary education; Web2.0

Human Computer Interaction using gestures for mobile devices and serious games: A review sotirios spanogianopoulos - Sirlantzis, Konstantinos; Mentzelopoulos, Markos; Protopsaltis, Aristidis (Proceedings of 2014 International Conference on Interactive Mobile Communication Technologies and Learning, IMCL 2014, 2015)
The Human-Computer Interaction (HCI) with interfaces is an active challenge field in the industry over the past decades and has opened the way to communicate with the means of verbal, hand and body gestures using the latest technologies for a variety of different applications in areas such as video games, training and simulation. However, accurate recognition of gestures is still a challenge. In this paper, we review the basic principles and current methodologies used for collecting the raw gesture data from the user for recognize actions the users perform and the technologies currently used for gesture-HCI in games enterprise. In addition, we present a set of projects from various applications in games industry that are using gestural interaction.
Created from Fastlane, Scopus look-up
Keywords: Augmented Reality (AR); Gesture Recognition; HCI; Hidden Markov Models (HMM); Support Vector Machines (SVM)

Implantación de un Sistema de Seguimiento de la Formación de los MOOC - Díaz, Pablo; Belda Anaya, Raquel; Eugenio, D ́Angelo; Formica, Costantino; Dimopoulou, Nefeli; Kazantzidou, Natassa; Protopsaltis, Aristidis; Schorer, Antonia; Gavalas, Damianos; Kostas, Apostolos; Makrides, Gregoris; Kyrillou, Roula (libro de resúmenes, 2021)

Learners’ User Experience Assessment of a Serious Game for Social Innovation Education - Schorer, Antonia; Protopsaltis, Aristidis (Proceedings of the 15th European Conference on Game Based Learning ECGBL 2021, 2021)
The use of serious games and game - based learning to develop new skills and knowledge in the context of social innovation education is a new and a promising endeavour. Social innovation education supports the empowerment and activation of students as social change makers. At the same time, the active engagem ent in socially impacted projects and activities enhances s elf - efficacy and promotes a positive emotional learning experience through game - based learning. Serious games are an opportunity for players - and learners - to demonstrate the impact of their actions in the creation and implementation of social innovation projects by working on emerging and real - world problems in a protected environment. To be able to achieve the educational goals of the game, the user experience of the learner during the game and learning process is crucial. A positive learning experience and appreci ation of the game, for instance in terms of usability and playability, will lead to more promising results than negative assessments. With the purpose of drawing conclusions in this context, the objective of this paper is to present the results of the user experience empirical analysis of learners in the NEMESIS Serious Games for Social Innovation. The game, based on an adventure and open - world game, introduces social innovation to students. This is achieved by bringing the player to NEMESIS City with the a im of increasing the well - being of the inhabitants with his "social innovation power". There, the player gets the opportunity to work on new problems and implement social innovation projects in collaboration with non - player characters (teachers, social inn ovators, parents’ , and other stakeholders) in order to be rewarded with happiness points for the city. The evaluation of the game focuses on usability/ playability, narratives, play engrossment, enjoyment, creative freedom, personal gratification, visual a esthetics and learning success of the game - based social innovation education approach. <br
Keywords: Serious Games; Game-based Learning; Social Innovation Education; Sustainable Development Goals; User Experience

Levels of interaction: A user-guided experience in large-scale virtual environments - Panzoli, David; Peters, Christopher; Dunwell, Ian; Sanchez, Stéphane; Petridis, Panagiotis; Protopsaltis, Aristidis; Scesa, Vincent; De Freitas, Sara (2nd International Conference on Games and Virtual Worlds for Serious Applications, VS-GAMES 2010, 2010)
This paper investigates a range of challenges faced in the design of a serious game, teaching history to a player immersed in an 'open' virtual environment. In the context of this paper, such an environment is described as an exploratory, expansive virtual world within which a user may interact in a non-linear, situated fashion with both the environment and virtual characters. The main contribution of this paper consists in the introduction of the levels of interaction (LoI), a novel framework designed to assist in the creation of interactions between the player and characters. The LoI approach also addresses the necessity for balancing computational efficiency with the need to provide believable and interactive virtual characters, by allowing varying degrees of animation, display and, ultimately, interaction detail. This paper demonstrates the challenges faced when implementing such a technique, as well as the potential benefits it brings. © 2010 IEEE.
Created from Fastlane, Scopus look-up

mEducator: multi type content repurposing and sharing in medical education - Protopsaltis, Aristidis; et al. (Learning and teaching in medicine, dentistry and veterinary medicine, 2010)

Outstanding teachers and ICT - Protopsaltis, Aristidis; Goodwyn, Andrew; Fuller, Carol L. (SIGDOC'09 - Proceedings of the 27th ACM International Conference on Design of Communication, 2009)
This paper presents evidence about expertise in teaching and the use of ICT (Information Communication Technology) to communicate information. Fifty four (54) expert teachers and teaching assistants from infant, primary and secondary schools participated in the study. Participants were nominated by their peers as 'outstanding' in their practice. Semi-structured interviews were conducted, exploring what technology experts have adapted to produce highly effective practice. The current study discusses the results of the demographic data, the technologies expert practitioners use in their teaching and their reasons for using these technologies. © 2009 ACM.
Created from Fastlane, Scopus look-up
Keywords: Expert teaching; ICT; Information processing; Learning; Technology

Overcoming the impact of parental gender bias and parents’ previous experiences on STEM teaching - Kikis-Papadakis, Kathy; Chaimala, Foteini; Protopsaltis, Aristidis; Schorer, Antonia; Nikolova, Nikolina; Firssova, Olga; Barajas, Mario; Salamon, Eszter (European Research Network About Parents in Education Conference - ERNAPE 2019, 2019)

Panel design of communication - Pierce, Robert; Mehlenbacher, Brad; Costa, Carlos, J.; Albers, Michael J; Protopsaltis, Aristidis (SIGDOC '08, 2008)
SIGDOC comes from a technical writing tradition, where literature and rhetoric play an important role. Communication is now giving a broader focus, especially as influences come from graphical design, web design, digital sound or digital multimedia. In Lisbon, we expect to discuss this focus of SIGDOC. This is an important transition that is being done, without loosing its identity. In fact, from the revision process the heterogeneity of view point was identified. This is the result of including more participants from multimedia, computer science and graphical design. For the second time, SIGDOC will take place outside the American continent. For the first time it takes places in a non-English speaking country. It is the ideal place to discuss an important issue either for the technical documentation, either for software engineering or for design of communication communities: translation, internationalization, localization, and globalization. Bologna process is transforming and making an authentic revolution in the European university panorama. This may be faced either as a threat or as an opportunity. In this context, the discussion about a curriculum in design of communication is an important step that may be undertaken by the SIGDOC. It is a step that may contribute to its affirmation either in academia or in practitioner context. <br

Perceptually captured gesture interaction with immersive information retrieval environments: An experimental framework for testing and rapid iteration - Mentzelopoulos, M.; Ferguson, J.; Protopsaltis, Aristidis (Interactive Mobile Communication Technologies and Learning (IMCL), 2015)

Perceptual User Interface Framework for Immersive Information Retrieval Environments: An Experimental Framework for Testing and Rapid Iteration - Mentzelopoulos, Markos; Ferguson, Jeffrey; Protopsaltis, Aristidis (International Journal of Interactive Mobile Technologies (iJIM), 2016)
The use of perceptual inputs is an emerging area within HCI that suggests a developing Perceptual User Interface (PUI) that may prove advantageous for those involved in serious mobile games and immersive social network environments. Since there are a large variety of input devices, software platforms, possible interactions, and myriad ways to combine all of the above elements in the pursuit of a PUI, we propose in this paper a basic experimental framework that will be able to standardize study of the wide range of interactive applications for testing efficacy in learning or information retrieval and also suggest improvements to emerging PUIs by enabling quick iteration. This rapid iteration will start to define a targeted range of interactions that will be intuitive and comfortable as perceptual inputs, and enhance learning and information retention in comparison to traditional GUI systems. The work focuses on the planning of the technical development of two scenarios, and the first steps in developing a framework to evaluate these and other PUIs for efficacy and pedagogy.<br
Keywords: perceptual; Perceptual User Interface (PUI); Human Computer Interaction (HCI); serious games; Graphical User Interface (GUI)

Proceedings of the 2011 Workshop on Open Source and Design of Communication - OSDOC '11 - Costa, Carlos, J.; Protopsaltis, Aristidis (2011)

Proceedings of the 26th annual ACM international conference on Design of communication - SIGDOC '08 - O'Neill, Henrique; Aparicio, Manuela; Costa, Carlos, J.; Protopsaltis, Aristidis (2008)

Proceedings of the 29th ACM international conference on Design of communication - SIGDOC '11 - Protopsaltis, Aristidis; Spyratos, Nicolas; Costa, Carlos, J.; Carlo, Meghini (2011)

Proceedings of the 29th International Conference on Design of Communication - Protopsaltis, Aristidis; Spyratos, Nikolaos; Costa, Carlos, J.; Carlo, Meghini (ACM Press, 2011)
Keywords: Design of Communication

Promoting cross-cultural awareness through exposure in Game-based Learning - Arnab, Sylvester; Protopsaltis, Aristidis; Minoi, J.L.; Dunwell, Ian; de Freitas, Sara (IEEE Learning Technology Newsletter, 2010)

Quiz Cube: An AR mobile learning application - Protopsaltis, Aristidis; Mentzelopoulos, Markos; Ferguson, Jeffrey; Kaloyan, Kanchev (Proceedings - 11th International Workshop on Semantic and Social Media Adaptation and Personalization, SMAP 2016, 2016)
The current paper presents the Quiz Cube application and its evaluation. The Quiz Cube application is an AR mobile learning application for students and teachers to easily make and use AR UI system using fiducial marker cubes. AR as a platform is just now reaching its full potential. Since smartphones and mobile devices are now at a sufficiently large user base, it is worth looking at the potential for an extremely small form factor delivery system that is flexible, easily modified, and used by educators and students. An easily modifiable AR learning experience will present an AR Mobile platform development, interactive museums, and the chosen subject in a new style. This method can be shown to improve not only knowledge of the chosen subject through investigation, but a better understanding of development potentials for the mobile devices now ubiquitous to students. The Quiz Cube application was evaluated in three different ways and the results are presented here.
Created from Fastlane, Scopus look-up
Keywords: Augmented Reality (AR); mobile learning; Quick Response Code (QR); User Interface (UI)

Reading Strategies in Hypertexts and Factors Influencing Hyperlink Selection - Protopsaltis, Aristidis (Journal of Educational Multimedia and Hypermedia, 2008)

Repurposing, Integrating, and Rating Serious Games as Learning Objects - Hendrix, Maurice; Protopsaltis, Aristidis; Dunwell, Ian; Petridis, Panagiotis; Arnab, Sylvester; de Freitas, Sara (Technological and Social Environments for Interactive Learning, 2013)
Keywords: Serious Games; learning objects; repurposing

Repurposing serious games in health care education - Protopsaltis, Aristidis; Panzoli, D.; Dunwell, I.; De Freitas, S. (IFMBE Proceedings, 2010)
Serious games are one of the most content-rich forms of educational media, often combining high fidelity visual and audio content, novel interaction paradigms, and diverse pedagogic approaches. This article describes exploratory work towards identifying the key issues faced when repurposing serious games in order to enable their use and reuse in the same or different educational contexts. To address these issues, we propose a theoretical framework for the repurposing of serious games in medical education and in education in general. Two case studies based on the Climate Health Impact serious game are presented. These case studies demonstrate the ability to repurpose a serious game into new learning objects, covering two different paradigms of content repurposing - language and pedagogy. © 2010 International Federation for Medical and Biological Engineering.
Created from Fastlane, Scopus look-up
Keywords: E-Health; Health Education; Metadata; Repurposing; Serious Games

Scenario-based serious games repurposing - Protopsaltis, Aristidis; Auneau, Laurent; Dunwell, Ian; De Freitas, Sara; Petridis, Panagiotis; Arnab, Sylvester; Scarle, Simon; Hendrix, Maurice (SIGDOC'11 - Proceedings of the 29th ACM International Conference on Design of Communication, 2011)
Serious games are very content-rich forms of educational media, often combining high fidelity visual and audio content with diverse pedagogic approaches. This paper introduces scenario-based serious games repurposing and demonstrates repurposing a serious game into new learning objects. The process uses the scenario editor called "mEditor". Two case studies based on the Happy Night Club serious game are presented. The article describes exploratory work which continues the work that started within the mEducator project regarding repurposing serious games in order to enable their use and reuse in the same or different educational contexts. © 2011 ACM.
Created from Fastlane, Scopus look-up
Keywords: interactive learning environments; media in education; serious games; simulations; virtual reality

Serious Games and Formal and Informal Learning - Protopsaltis, Aristidis; Pannese, Lucia; Pappa, Dimitra; Hetzner, Sonia (eLearning papers, 2011)

Serious games - Protopsaltis, Aristidis (Eurosigdoc Workshop on Open Source and Design of Communication, 2010)
The talk will introduce Serious Games to the audience, discuses the current state of the art in the field with the use of case studies. Furthermore the different pedagogical approaches to learning with the use of serious games will be presented and discussed. Finally, some of the current projects at the Serious Games Institute will be show cased.<br

Serious Games in Formal and Informal Learning - Hetzner, Sonia; Protopsaltis, Aristidis; Pappa, Dimitra; Pannese, Lucia (eLearning papers, 2012)

SIGDOC '09: Proceedings of the 27th ACM international conference on Design of communication - Protopsaltis, Aristidis; Mehlenbacher, Brad; Williams, Ashley; Slattery, Shaun P (2009)

Simulation game for training new teachers in class management - Bouki, Vassiliki; Mentzelopoulos, Markos; Protopsaltis, Aristidis (SIGDOC'11 - Proceedings of the 29th ACM International Conference on Design of Communication, 2011)
Games are used in education at all levels for quite long time. Most educational games intend to introduce trainees to a new subject and present them with new knowledge when others allow then to acquire and improve certain skills. This paper presents the "Teaching Game", an implementation that explores the possibility to create a simulation of a classroom event in the format of a game. It is offered as a training tool for new teachers who want to get prepared for the class. The educational aim of the game is to put players in the place of a teacher who comes across some unforeseen circumstances and to allow them to test and improve their skills in class management. The 'teaching game' has been implemented in Game Maker 7 and it is a tool developed for the needs of the "Virtual Training Environment (VTE) for Teachers" at the University of Westminster. © 2011 ACM.
Created from Fastlane, Scopus look-up
Keywords: simulation

Small and flexible web based framework for teaching QR and AR mobile learning application development - Protopsaltis, Aristidis; Ferguson, J.; Mentzelopoulos, M.; Economou, D. (2015 International Conference on Interactive Mobile Communication Technologies and Learning (IMCL), 2015)
The current paper presents an AR development framework for students to easily make and use small QR linked interactive learning web pages on mobile devices targeted primarily for museums. This framework is extrapolated from an AR UI system using fiducial marker cubes. AR as a platform is just now reaching its full potential. Since smartphones and mobile devices are now at a sufficiently large user base, it is worth looking at the potential for an extremely small form factor delivery system that is flexible, easily modified, and used by educators and students. An easily modifiable AR learning experience will present AR, QR Mobile platform development, interactive museums, and the chosen subject in a new style. This method of flipped learning can be shown to improve not only knowledge of the chosen subject through investigation, but a better understanding of development potentials for the mobile devices now ubiquitous to students.<br
Keywords: flipped; mobile learning; Augmented Reality (AR); User Interface (UI); QR

Social Innovation Education and Social Innovation Skill Development - Garefi, Ioanna; Kalemaki, Irene; Schorer, Antonia; Protopsaltis, Aristidis (ICERI2020 Proceedings, 2020)
Social Innovation Education (SIE) is a new educational concept that is different from Entrepreneurship Education (EE), Citizenship Education (CE) and Education for Sustainable Development (ESD). SIE is a collaborative and collective learning process for the empowerment and socio/political activation of students to drive positive change no matter their professional pathways. SIE builds students’ competences to identify opportunities for social value creation, to form collaborations and build relationships and take innovative action for a more democratic and sustainable society [1]. Its effect on learning has a threefold objective, to empower students by actively engaging them as co-creators of their learning activities, to socio-politically activate them to drive social change and finally, to develop the necessary competences for a more democratic and sustainable society. In the context of the NEMESIS Horizon2020 project, a Social Innovation Learning Framework (SILF) was developed together with a social innovation competence framework containing 14 competences, with 4 levels of development [1]. The emphasis of the social innovation competences is placed on the collective ability to identify opportunities and take action alongside individual abilities to form relationships and participate effectively in collaborative learning and decision-making. The social innovation competence framework was evaluated as part of the SILF in a yearlong pilot study, in 5 European countries. A realistic evaluation approach was employed to evaluate how students were impacted and how their competences were developed by their involvement in the design, co-creation and implementation of social innovation projects. 56 teachers, 1030 students and 69 local community actors from 5 different European countries (GR, FR, ES, PT, UK) took part in the evaluation. However, 206 students have participated in the post-assessment survey regarding the competences and the results presented here have also taken into account the feedback from teachers, Social Innovation Practitioners (SIP) and parents. The majority of the results have shown a positive impact of SIE on social innovation competence development with many students progressing through different level of competences and becoming more socially aware and competent. For instance, regarding the competence “vision for a better world” Greek students indicated that their level of competence progression they indicated that they have reached a level 3 (41%) whereby Spanish students reached level 4 (42%), both from level 2. In both cases, the results revealed that SIE helped their social innovation competence development in significant way. Similarly, for the “social resilience” competence 39% of Greek students and 25% of Spanish students indicated reaching Level 3, while 38% of Greek students and 31% of Spanish indicated reaching Level 4. 23% of Spanish students and 7% of Greeks were still at Level 1 and 21% and 15% of Spanish and Greek students respectively reached Level 2. Similar results were revealed for most of the other competences. Finally, the results revealed that assessing the level or progress of competence development is indeed an ongoing process in which knowledge and skills are continually built. It is not something that can be harnessed in a short-term period but something that needs continuous efforts.<br
Keywords: innovation; social innovation; social innovation education

Social Innovation Education in European Higher Education - Pouliopoulos, Theofilos; Schorer, Antonia; Garefi, Ioanna; Kalemaki, Irene; Galvan, Cristina; Barajas, Mario; Theodoridou, Katerina; Kouros, Thodoris; Fuduric, Morana; Mavrogeni, Stavroula; Wittine, Zoran; Protopsaltis, Aristidis (Proceedings of 12th International Social Innovation Research Conference, 2022)
Social Innovation Education (SIE) is a unique teaching and learning approach that features certain principles. Its contribution according to Rivers et al (2015) is four-fold. It promotes systemic and sustainable approaches to improving society through positive social change. It aims to develop qualities for positive change-making in students, such as those referred to as “attributes for social innovation.” It subsumes the development of employability skills and twenty-first-century skills, while working toward a more sophisticated set of competencies and finally promotes learning on a more critical and socially impactful plane than traditional undergraduate education. (Alden-Rivers, et al., 2015, p. 3) This paper as part of the EC project (BUFSIE) examines the current statues of SIE in HE in five European countries (DE, GR, CY, ES, HR). To capture existing notions and experiences regarding SIE in HEIs, an online survey was conducted with university professors and HEI teaching staff. Particularly, 55 HEI professors, teachers and researchers from 5 countries participated in the online survey and allowed us to map and analyse the context of SI and SIE in HEIs. For the assessment of the current situation, the Assessment for learning Audit Instrument (AfLAi) was selected, due to its usability for the educators’ context. The AfL is a methodology to support schools in conducting site-based reviews of their current knowledge, skills and practices in formative assessment. Our assessment tool has embedded the assessment scale of the AfL and the design philosophy. The utmost goal of this assessment process was to map the context of each university, in order to design the best possible intervention regarding SIE. In other words, “any assessment for which the first priority in its design and practice is to serve the purpose of promoting pupils’ learning” (Black et al., 2002, p. 1). The present assessment tool has been designed to assess the level of awareness and integration of Social Innovation Education (SIE) in the countries that participate in the implementation phase of the BUFSIE project. The assessment process is divided into 3 specific areas, which are of course the design principles of SIE: Student at the center Co-creation process Transformative social action The results revealed that the concept of SIE is a rather new term in the HEIs’ context of our study. In some countries, like in Croatia, it is an emerging field, while in others the existence of SIE elements appears to depend on the discipline or the field of study. However, the perception of both educators and students about SIE is more than positive. In fact, it is so positive that students in particular call for an institutionalization of SIE in the standard curriculum and a connection with the ECTS system

Social Innovation Education in Primary and Secondary Education: An Evaluation - Protopsaltis, Aristidis; Garefi, Ioana; Kalemaki, Irene; Schorer, Antonia (Proceedings of 12th International Social Innovation Research Conference, 2022)
This paper provides an overview of the evaluation results obtained during the second pilot period of the NEMESIS Horizon2020 project. The findings reflect upon the impact of implementing the SIE model of NEMESIS and its components on both students and teachers (and when possible, on other involved stakeholders). The NEMESIS Social Innovation Education (SIE) model consists of three layers, the foundational layer which offers the underlying educational philosophy; the middle layer that provides the design principles used for the structural elements and the top layer offers some context-sensitive program components that allow SIE to be tailored to different local settings and serve for different interpretations of achieved outcomes. The evaluation method used is the realistic evaluation approach. This approach is examining how students were impacted by their involvement in the design, co-creation and implementation of their social innovation projects (Pawson & Tilley, 1997). The evaluation tools used included online surveys for students, teachers, external stakeholders and focus groups with teachers and head teachers. This pilot period included 22 schools in total. Ten (10) schools from the Netherlands however implemented the SIE model through a lesson series and were excluded from the evaluation given that the lesson series approach does not fully appreciated the NEMESIS SIE approach and it has been supplementary of the NEMESIS project that could be followed by prospective schools either as a one-off project or in combination with the SIE model. The data have yielded several key lessons. The most important aspect of NEMESIS was that children felt not only included but in charge of their own projects and this translated directly into increased interest and engagement. Furthermore, the data revealed that is significantly impacting upon improving human relationships among students and helping especially those shy and introvert to step forward and proactively participate in the school life. All in all, student-adult interactions have been very engaging and at the same time very valuable not only for students but also for adults themselves. Apart from supporting the co-creation labs with equipment, the involvement of external stakeholders has been beneficial as they have shared knowledge with the students that the teachers themselves would never be able to do so. Finally, the data has shown that SIE had a positive impact on student’s civic engagement largely as a result of their engagement with social issues and their interaction with external stakeholders, which helped them realise that they can influence change and better understand various social problem
Keywords: Social Innovation Education; Education; Realistic Evaluation

Socio-semantic Integration of Educational Resources - the Case of the mEducator Project - Dietze, Stephan; Kaldoudi, Eleni; Dovrolis, Nikolas; Protopsaltis, Aristidis; Giordano, Daniela; Spampinato, Concetto; Hendrix, Maurice; Taibi, Davide; Yu, Hong Qing (Journal of Universal Computer Science, 2013)
Research in technology-enhanced learning (TEL) throughout the last decade has largely focused on sharing and reusing educational resources and data. This effort has led to a fragmented landscape of competing metadata schemas, such as IEEE LOM or ADL SCORM, and interface mechanisms, such as OAI-PMH, SQI and REST-ful services in general. More recently, semantic technologies were taken into account to improve interoperability. However, so far web-scale integration of resources is not facilitated, mainly due to the lack of take-up of shared principles, datasets and schemas. On the other hand, the Linked Data approach has emerged as the de facto standard for sharing data on the Web and is fundamentally based on established W3C standards. This paper presents results of the European Commission-funded project mEducator, which exploits Linked Data principles for (1) semantic integration and (2) social interconnecting of educational data, resources and actors. We describe a general approach to exploit the wealth of already existing educational data on the Web by allowing its exposure as Linked Data and by taking into account automated enrichment and interlinking techniques to provide a rich and well-interlinked graph for the educational domain. Additionally, the paper presents an evaluation of our work with respect to a set of socio-semantic dimensions. Experimental results demonstrate improved interoperability and retrievability of the resulting resource descriptions as part of an interlinked resource graph. We describe a general approach to exploit the wealth of already existing educational data on the Web by allowing its exposure as Linked Data and by taking into account automated enrichment and interlinking techniques to provide a rich and well-interlinked graph for the educational domain. Additionally, the paper presents an evaluation of our work with respect to a set of socio-semantic dimensions. Experimental results demonstrate improved interoperability and retrievability of the resulting resource descriptions as part of an interlinked resource graph. We describe a general approach to exploit the wealth of already existing educational data on the Web by allowing its exposure as Linked Data and by taking into account automated enrichment and interlinking techniques to provide a rich and well-interlinked graph for the educational domain. Additionally, the paper presents an evaluation of our work with respect to a set of socio-semantic dimensions. Experimental results demonstrate improved interoperability and retrievability of the resulting resource descriptions as part of an interlinked resource graph. the paper presents an evaluation of our work with respect to a set of socio-semantic dimensions. Experimental results demonstrate improved interoperability and retrievability of the resulting resource descriptions as part of an interlinked resource graph. the paper presents an evaluation of our work with respect to a set of socio-semantic dimensions. Experimental results demonstrate improved interoperability and retrievability of the resulting resource descriptions as part of an interlinked resource graph.<br
Keywords: Linked Data; Semantic Web; SOA: Technology-enhanced Learning; Clustering

StartUP_EU: Using game-based learning and Web 2.0 technologies to teach entrepreneurship to secondary education students - Protopsaltis, Aristidis; Hetzner, Sonia; Borotis, Spiros; Connolly, Thomas; Hainey, Thomas (7th European Conference on Games Based Learning, 2013)

The effects of reading goals in hypertext reading - Protopsaltis, Aristidis; Bouki, Vassiliki (ACM SIGDOC 2006 - Proceedings of the 24th ACM International Conference on Design of Communication, 2006)
The present study examined the influence of different reading goals on reading in a hypertext environment. The study focused on text based electronic documents. The study was an independent samples design experiment with three different conditions. Ninety participants read the hypertext allocated into three different conditions and then, all answered the same set of questions. The results show that reading goals did not influence reading times, comprehension scores, and amount of visited links. The data also revealed two factors that influence hyperlink selection: coherence, and location © 2006 ACM.
Created from Fastlane, Scopus look-up
Keywords: cognitive processes; coherence; comprehension; hypertext; reading goals

The NEMESIS Social Innovation Learning Platform - Protopsaltis, Aristidis; Copado Mejías, Jesús; Schorer, Antonia; Garefi, Ioana; Kalemaki, Irene (Proceedings of 11th International Social Innovation Research Conference, 2020)
This paper presents the NEMESIS Social Innovation Open Learning Platform (SIOLP) and its evaluation results during piloting in 5 European countries. The NEMESIS SIOLP is an open adaptive and evolving platform, based on ILIAS open source software, that ensures access to SI education for all. Existing educational programs on social innovation or on social entrepreneurship education are limited, while they cannot be accessed by all. Additionally , there is no platform that supports Social Innovation Education (SIE). The NEMESIS SIOLP offers the tools and resources to all teachers, trainers and educators around Europe to adopt the NEMESIS social innovation education model in an easy and effective way. The platform provides open access to useful resources for teachers but also an online knowledge sharing space for students. Particularly, For the evaluation of the NEMESIS SIOLP, a single-factor design has been used, using two different questionnaires during the pre-pilot evaluation. The System Usability Scale (SUS) developed by Brooke (1996) and the IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999). The SUS questionnaire was modified to include some more task specific questions to fit the NEMESIS tasks. The IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999) is a user-oriented approach to software evaluation and its short version was used. Additionally, a realistic approach was used during the pilot phase. A realistic approach to evaluation permits us to understand under what circumstances complex interventions work or fail (Pawson & Tilley, 2004). The results presented in this paper refer to the first complete evaluation of the “alfa” version of the system in 5 European counties and 8 schools. The survey was anonymous and the participants had to complete a set of tasks before they answered the questionnaire. The evaluation results have shown that the NEMESIS SIOLP largely supports the stakeholders' needs but usability issues were identified
Keywords: Social Innovation; Social Innovation Education; Open Learning Platform; Evaluation

The NEMESIS Social Innovation Open Learning Platform: An Evaluation - Protopsaltis, Aristidis; Copado Mejías, Jesús; Garefi, Ioana; Kalemaki, Irene; Kantsiou, Sofia (ISIRC Book of Abstracts, 2019)

The NEMESIS Social Innovation Open Learning Platform: An Evaluation - Protopsaltis, Aristidis; Copado Mejías, Jesús; Garefi, Ioana; Kalemaki, Irene; Kantsiou, Sofia (7th EMES International Research Conference on Social Enterprise 2019, 2019)
NEMESIS stands for New Educational Model Enabling Social Innovation Skills development and it is a Horizon 2020 project. It envisages the development of a new educational model that will harvest students’ knowhow and further build on their inherent competences as a means of improving their capabilities and drive social change. This process will enable students to become creative social thinkers, develop entrepreneurial mind-sets and become social change makers into a world where inequality, poverty and social exclusion are still quite evident. The NEMESIS approach is based on principles of participatory pedagogies focusing on collective learning and co-creation of new knowledge. NEMESIS introduces new relations and processes whereby students are empowered to create their learning paths during a process that emerges through participation and active engagement with others. To assist this process, the NEMESIS Social Innovation Open Learning Platform (SIOLP) has been developed. NEMESIS SIOLP is an open adaptive and evolving platform, based on ILIAS open source software, that ensures access to SI education for all. Existing educational programs on social innovation or on social entrepreneurship education are limited, while they cannot be accessed by all. Additionally, there is no platform that supports Social Innovation Education (SIE). The NEMESIS SIOLP offers the tools and resources to all teachers, trainers and educators around Europe to adopt the NEMESIS SIE model in an easy and effective way. The platform provides open access to useful resources for teachers but also an online knowledge sharing space for students. Particularly, the NEMESIS platform is offering access to: a) guides and training material for using the NEMESIS model, b) educational resources aiming at introducing Social Innovation philosophy and competences to students, c) access to the members of the Social Innovation Practitioners (SIP) community, d) and finally access to an online collaborative environment. The main features of the NEMESIS SIOLP include: a flexible Course Management for a multitude of didactical scenarios and study programs that allow the reproduction of full curriculums with a single tool. Additionally, content sharing with fast Drag & Drop File Upload, a personal workspace for learners, allowing the easy creation of blogs, simple creation of study materials with authoring tools such us build learning modules, wikis, glossaries, and much more. Furthermore, the platform enables a large number of integrated communication tools such as personal profiles, contacts, who is online?-tool, mail, chat and more. A general characteristic of the NEMESIS SIOLP is the ILIAS concept of Personal Desktop and Repository. While the Repository contains all content, courses and other materials structured in categories and described by metadata, the Personal Desktop is the individual workspace of each learner, author, tutor and administrator. The Personal Desktop contains selected items from the as well as certain tools like mail, tagging, a calendar and also e-portfolio and personal blogs. For the evaluation of the NEMESIS SIOLP a single-factor design has been used, using two different questionnaires. The System Usability Scale (SUS) developed by Brooke (1996) and the IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999). The SUS questionnaire is an effective tool for global assessing the system’s usability consisting of ten items. The SUS questionnaire was extended to include some more task specific questions to fit the NEMESIS tasks. The IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999) is user-oriented approach to software evaluation. The short version of the IsoMetrics inventory, which comprises 75 items, was used. Those items are aiming to operationalise the seven dialog design principles of the international standard ISO 9241-10: i) Suitability, ii) Self Descriptiveness, iii) Controllability, iv) Conformity with user expectations, v) Error Tolerance, vi) Suitability for individualization and vii) Suitability for learning. The results presented here refer to the first internal evaluation of the “alfa” version of the system. Twelve users took part in the survey. The survey was anonymous and the participants had to complete a set of tasks before they answered the questionnaire. The evaluation results have shown that the NEMESIS SIOLP largely supports the stakeholders’ needs by performing the tasks it was planned to perform, in a coherent and user-friendly way. The majority of participants found the platform easy to use, not complex at all and felt confident in using i

The Value of Team-Based Mixed-Reality (TBMR) Games in Higher Education - Denholm, John; Protopsaltis, Aristidis; de Freitas, Sara (6th European Conference on Games Based Learning (ECGBL 2012), 2012)

The values Team-Based Mixed-Reality (TBMR) Games in Higher Education - Denholm, John; Protopsaltis, Aristidis; de Freitas, Sara (International Journal of Game-Based Learning, 2013)
Keywords: Game-based learning; Mixed reality games; Serious Games

THE VOICE OF E-LEARNERS - D´Angelo, Eugenio; Formica, Costantino; Dimopoulou, Nefeli; Kazantzidou, Natassa; Protopsaltis, Aristidis; Schorer, Antonia; Gavalas, Damianos; Kostas, Apostolos; Makrides, Gregoris; Kyrillou, Roula; Capablanca Francés, Lucía; Belda Anaya, Raquel (16th International Technology, Education and Development Conference, 2022)
In recent years, online learning has experienced a remarkable demand from students who want to complete their training and improve their professional skills and job position, being able to adapt this training to their pace of life. The pandemic situation due to Covid has made this increase more evident and the platforms that offer MOOCs and online training have seen a striking increase in enrolment in their courses. Due this high demand for courses online, it is necessary to evaluate whether this training is fulfilling its purpose. The main objective of any quality management system is customer satisfaction. In order to determine the degree of satisfaction, an appropriate measurement system is required to obtain qualitative and quantitative quality information in order to be able to make decisions and establish proposals for improvements aimed at achieving the objective of satisfying the customer, the learner. With the data gathered in the pilot run of the tracking tool developed in the ASTRE project, the voice of the learner has been heard. These data have been analysed and general recommendations for MOOC and e-learning providers have been issued. This important feedback can help to detect improvements and/or establish the strengths of the training offere
Keywords: improve; quality; egressed; tracking; survey

Towards a hypertext reading/comprehension model - Protopsaltis, Aristidis; Bouki, Vassiliki (Proceedings of the 23rd International Conference on Design of Communication - Documenting and Designing for Pervasive Information, 2005)
This paper reports on a study that is concerned with the cognitive aspects of reading in a hypertext environment. The study focuses on text based electronic documents. A cognitive model for hypertext document reading proposed in an earlier work is here developed and validated with the use of think aloud protocols. Navigational strategies that readers employ in hypertext reading and hypertext links' selection are also under study. The results indicate that 100% of the task related data correspond to the components of the cognitive model, allowing us to conclude that the proposed model sufficiently describes the cognitive processes involved in hypertext reading. In addition, three navigational strategies are revealed: linear, mixed, and mixed review. The quantitative data show no significant differences between different reading goals and comprehension. Copyright 2005 ACM.
Created from Fastlane, Scopus look-up
Keywords: Cognitive Processes; Comprehension; Hypertext; Reading Strategies

Towards a learning framework for Social Innovation Education - Kalemaki, Irene; Garefi, Ioana; Kantsiou, Sofia; Diego, Ivan; Protopsaltis, Aristidis; Wall, Jen (EMES Selected Conference Papers, 2019)
Keywords: Social Innovation; Social Innovation Education; learning framework; empowerment; sociopolitical activation; competences

Tracking, a necessity to improve online learning - Protopsaltis, Aristidis; Schorer, Antonia; Gavalas, D.; Triantis, Kostas; Makrides, G. A.; Kyrillou, R; Dimopoulou, N; Kazantzidou, N.; D´Angelo, E.; Formica, C.; Díaz-García, P.; Gisbert-Payá, J. (Proceedings of INTED2021 Conference, 2021)
At this moment, pandemic situation due to COVID-19 implies some changes, there is a considerable transformation for the digital system, not only work has moved to online when possible but also education had to move fast to online learning in the majority of developed countries. ASTRE project is focused in improving the quality of offered online learning opportunities for adults which is directly related with the requirements from the pandemic. This paper is the preliminary result from ASTRE project, a project based on Online Learning for adults and its impact. The aim of this paper is to study different MOOC (Massive Open Online Courses) providers in order to analyse existing tracking systems. MOOC providers have been mapped at international level. A survey has been created and launched and in depth interviews have been conducted. Despite finding some universities with no tracking system, results show many organisations or universities with online learning, implement somehow a tracking system to monitor the students. What is really surprising, is the fact that, once the student is not enrolled in the organisation, there is not any further contact. Consequently, there is no information on the impact online learning had on the learner’s personal and professional competences. A common response from every survey was the importance given to track the studen
Keywords: Monitor; MOOC; active learning; survey; egressed

weSPOT: A Personal and Social Approach to Inquiry-Based Learning - Mikroyannidis, Alexandros; Okada, Alexandra; Scott, Peter; Rusman, Elen; Specht, Marcus; Stefanov, Krasenn; Protopsaltis, Aristidis; Held, Paul; Hetzner, Sonia; Kikis-Papadakis, Kathy; Chaimala, Foteini (Journal of Universal Computer Science, 2013)
Keywords: Inquiry-based learning; scientific inquiry; personal learning environment; cloud learning environment

weSPOT: A Personal and Social Approach to Inquiry-Based Learning - Protopsaltis, Aristidis; Hetzner, Sonia; et al. (Journal of Universal Computer Science, 2013)
weSPOT is a new European initiative proposing a novel approach for personal and social inquiry-based learning in secondary and higher education. weSPOT aims at enabling students to create their mash-ups out of cloud-based tools and services in order to perform scientific investigations. Students will also be able to share their inquiry accomplishments in social networks and receive feedback from the learning environment and their peers. This paper presents the research framework of the weSPOT project, as well as the initial inquiry-based learning scenarios that will be piloted by the project in real-life educational settings.
Keywords: social learning; scientific inquiry; personal learning environment; cloud learning environment; inquiry-based learning

What is design of communication? - Pierce, Robert; Protopsaltis, Aristidis; Mehlenbacher, Brad; Zachry, Mark (SIGDOC07, 2007)
What is the Design of Communication? In this panel, four SIGDOC members from different areas come together to discuss the interdisciplinary area of DOC.<br
Keywords: Human-centered computing; Human computer interaction (HCI)

Working Environment with Social and Personal Open Tools for Inquiry-Based Learning Pedagogic and Diagnostic Frameworks - Protopsaltis, Aristidis; Seitlinger, C; Chaimala, Foteini; Firssova, Olga; Hetzner, Sonia; Kikis-Papadakis, Kathy; Boytchev, Pavel (The International Journal of Science, Mathematics and Technology Learning, 2014)
The weSPOT project aims at propagating scientific inquiry as the approach for science learning and teaching in combination with today's curricula and teaching practices The project focuses on inquiry-based learning with a theoretically sound and technology supported personal inquiry approach and it contains three main development aspects: (a) define a reference model for inquiry-based learning skills, (b) create a diagnostic instrument for measuring inquiry skills, and (c) implement a working environment that allows the easy linking of inquiry activities with school curricula and legacy systems. The current work outlines the pedagogical and diagnostic frameworks for scientific inquiry. The pedagogical framework is aimed at supporting informal, self-regulated learning settings as well as the embedding in a formal learning context. The scientific exploration process can take place independently, or in collaboration with others. The diagnostic framework focuses on the pedagogical diagnosis, which will be tailored to the ambitious aim of inferring students' inquiry and meta-cognitive skills as well as domain-specific knowledge from observational data tracked within the weSPOT environment. Pilot studies planned to be conducted in 16 test beds across 6 EU countries will test the reference model and make use of the diagnostic instrument. inquiry and meta-cognitive skills as well as domain-specific knowledge from observational data tracked within the weSPOT environment. Pilot studies planned to be conducted in 16 test beds across 6 EU countries will test the reference model and make use of the diagnostic instrument. inquiry and meta-cognitive skills as well as domain-specific knowledge from observational data tracked within the weSPOT environment. Pilot studies planned to be conducted in 16 test beds across 6 EU countries will test the reference model and make use of the diagnostic instrument.<br
Keywords: Inquiry-based Learning; Mobile Technologies; Pedagogic Framework; Diagnostic Framework